The Power of Crowdcourcing and Participatory Culture: Beauty Vlogger Analysis on Wardah Cosmetic Brand - Atikah Putri Adrilia Gultom (Universitas Negeri Medan, 2021)
Advances in technology and the internet have fundamentally changed the way we consume media and generate innovation, including in the fields of advertising and marketing. Participatory culture and crowdsourcing by beauty vloggers change the power patterns (top-down, bottom-up or both) that the industry has in implementing advertising strategies. In addition, the strength of individuals in a participatory culture arises because of various media such as video blogs or websites that allow individuals to share comments and reviews. This situation provides an opportunity for beauty vloggers with the power they have to distribute their power, so that strength is not absolutely in the industry. Meanwhile, from the industry side, you can use beauty vlogger services to become a marketing strategy. This conceptual paper uses literature review and meta-synthesis methods to discuss the power possessed by beauty vloggers through participatory culture and crowdsourcing as well as linking it to Wardah cosmetic products as one of the products using the halal concept. The purpose of this research is to see the power possessed by beauty vloggers can influence the public using the local makeup brand Wardah and Wardah power as a local halal makeup brand so that it is attractive to Muslim women. Finally, the analysis of this conceptual paper shows that participatory culture and crowdsourcing have become very important entities in the dynamics of the advertising and marketing industry in the digital era.